Electrochemical synthesis and tribological properties of flower-like and sheet-like MoS2 in LiClKCl(NH4)6Mo7O24KSCN melt. (1st May 2018) - Liu, Yu-Hui; Jing, Xiao-Yan; Zhang, Mi-Lin; Yan, Yong-De; Ji, De-Bin; Li, Peng; Xu, Heng-Bin; Xue, Yun
Abstract: Electrochemical co-reduction of Mo(VI) and S(II) was studied in LiClKClKCl(NH4 )6 Mo7 O24 KSCN melt, and the molybdenum disulfide (MoS2 ) with specially structures of flower-like and sheet-like molybdenum disulphide was successfully synthesized by molten salt electrolysis. This study investigated the influences of KSCN concentration, experimental temperature and current density on the formation of MoS2, and the controllability of MoS2 microstructure was successfully realized by adjusting the experimental temperature and current density. Simultaneously, the electrochemical behaviors of Mo(VI) and S(II) in the melt were investigated by cyclic voltammetry (CV), square wave voltammetry (SWV) and open-circuit chronopotentiometry (OCP). All of the MoS2 samples obtained by electrochemical co-reduction Mo(VI) and S(II) were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS), X-ray photoelectron spectroscopy (XPS), high-resolution TEM (HRTEM) and pin-on-disc friction and wear machine, respectively. The results from tribological properties tests illustrated that MoS2, as a solid lubricant, has the low friction coefficient and good wear resistance. The friction coefficient of flower-like MoS2 is around 0.119.